VocBlast: A Qualitative Evaluation on the Use Vocabulary Mobile App From Teachers’ Views - Zuraina, Ali; Mohd Amir Izuddin, Mohamad Ghazali (2015)
Technology brings everything under one roof especially through the development of mobile phones. Previously, everyone was excited about downloading new ringtone for their phones. It got even better through time when mobile phone users can use their preferred mp3 as a ringtone. Today, the iPhone and Android users are overwhelmed by the number of applications that can be downloaded to help them in daily lives. There are applications for health, productivity and photo editing. Recently, there has been renewed interest when educators integrate mobile learning (m-learning) in their teaching. VocBlast, for instance, is a newly-developed engineering vocabulary mobile application (app) that is developed to assist engineering students at tertiary level to improve their mastery of English language. The current study, therefore, reviews the content in VocBlast from the language teachers’ perspectives. E-mail interviews were conducted employing four (4) language teachers in Universiti Malaysia Pahang. Based on the result, the participants agreed that the use of VocBlast in teaching and learning process is very helpful and able to benefit both, teachers and students. The app provides an indirect learning experience to the latter. At the same time, the features that are available in the app are appropriate and useful. Although VocBlast is still in the progress of development, the result presented may facilitate improvements of the app itself. Other than that,VocBlast can be considered as a new alternative for students to diversify their vocabulary learning experience.